Using a national archive of patient experience narratives to promote local patient-centered quality improvement: an ethnographic process evaluation of 'accelerated' experience-based co-design. (October 2014) - Locock, Louise; Robert, Glenn; Boaz, Annette; Vougioukalou, Sonia; Shuldham, Caroline; Fielden, Jonathan; Ziebland, Sue; Gager, Melanie; Tollyfield, Ruth; Pearcey, John
Objectives: To evaluate an accelerated form of experience-based co-design (EBCD), a type of participatory action research in which patients and staff work together to improve quality; to observe how acceleration affected the process and outcomes of the intervention. Methods: An ethnographic process evaluation of an adapted form of EBCD was conducted, including observations, interviews, questionnaires and documentary analysis. Whilst retaining all components of EBCD, the adapted approach replaced local patient interviews with secondary analysis of a national archive of patient experience narratives to create national trigger films; shortened the timeframe; and employed local improvement facilitators. It was tested in intensive care and lung cancer in two English National Health Service (NHS) hospitals. A total of 96 clinical staff (primarily nursing and medical), and 63 patients and family members participated in co-design activities. Results: The accelerated approach proved acceptable to staff and patients; using films of national rather than local narratives did not adversely affect local NHS staff engagement, and may have made the process less threatening or challenging. Local patients felt the national films generally reflected important themes although a minority felt they were more negative than their own experience. However, they served their purpose of 'triggering' discussion between patients and staff, and the resulting 48 co-design (improvement) activities across the four pathways were similar to those in EBCD, but achieved more quickly and at lower cost. Conclusions: Accelerated EBCD offers a rigorous and relatively cost-effective patient-centered quality improvement approach.